Transformation of Education Organization Management in the Digital Age: Meeting the Challenges and Seizing the Opportunities - Bella, Bella Febrianti (Ittishal Educational Research Journal, 2025)
This research aims to identify and analyze the factors that influence the transformation of education in the digital era, as well as the role of management in improving the quality of education in this era. The method used in this research is a descriptive- qualitative approach using library research. The results show that several factors affecting educational change in the digital era include the knowledge, skills and beliefs of members of educational organizations, as well as a supportive organizational environment. Information technology plays an important role in improving the efficiency, effectiveness and strategic development of education. Education management, which includes aspects of planning, organizing and evaluating, plays a key role in improving the quality of education in a sustainable manner. In addition, this study also found that the implementation of proper management and the development of a modern organizational culture are necessary to face the challenges in the digital education world. Some important steps that can be taken to improve the quality of education in the digital era are optimizing the use of technology, improving infrastructure, developing digital skills for educators, and implementing innovative learning approaches. This research makes an important contribution in enriching the literature on education management in the digital era and can serve as a foundation for more effective education policies and practices in the future.